Frequency of mutations associated with resistance to first- and second-line drugs in multidrug-resistant Mycobacterium tuberculosis isolates. (September 2020) - Bitar, Ibrahim; Medvecky, Matej; Amlerova, Jana; Papagiannitsis, Costas C.; Hrabak, Jaroslav
Highlights: The proposed phylogeny approach can be used as a standard for Mycobacterium tuberculosis. The most dominant lineage in our study was lineage 4. The phenotypic resistance profile did not match that of the genotype in all cases. There is a need to update databases regarding the mechanism of resistance. Abstract: Introduction: Tuberculosis is considered one of the most fatal diseases worldwide, with an estimation of 10.1 million cases. In this study, whole-genome sequencing was used to determine the genomic characterisation of 40 Mycobacterium tuberculosis isolates from patients with different nationalities hospitalised in the Czech Republic. Materials and methods: Susceptibility testing for first-line drugs was performed. DNA was sequenced using the Illumina MiSeq platform. Spoligotype single-nucleotide polymorphisms and mutations in antibiotic-resistant genes were detected, and phylogenetic analysis was performed. Results: Samples showing phenotypic resistance to at least one drug were 12 to streptomycin, 11 to isoniazid, 7 to rifampicin, 6 to ethambutol and 5 to pyrazinamide. Phenotypic and genotypic profiles did not match in all cases, suggesting the presence of a novel mutation in some cases and a low expression of resistant genes in others. The presented phylogeny enables the correct assignation of M. tuberculosis lineages and sublineages. Our results suggest that the most dominant lineage in our samples was lineage 4 (33/40). Conclusion: To our knowledge, this is the first study using this approach to be done in the Czech Republic. Lineage 4 was the predominant lineage identified among our samples. Nevertheless, the dominance of Lineage 4 along with other lineages suggests that infections can originate from different sources.